Mercury Pollution Due to Small-Scale Gold Mining in the Philippines: An Economic Analysis - Aniceto C. Orbeta; Danilo C. Israel; Jasminda Asirot (Philippine Institute for Development Studies (PIDS), 2000)
The study reviews small-scale gold mining in the Philippines and economically assesses mercury pollution and other development problems in the industry. The end purpose is to suggest measures to address the problems and promote better environmental and overall management of small-scale mining. The study has used secondary data from mining institutions and primary data from key informants and small-scale gold miners and processors in the two case study sites.
Keywords: 330; natural resources and environment; environmental issues; environmental management; Goldbergbau; KMU; Quecksilber; Gewässerbelastung; Umweltökonomik; Philippinen